2018
DOI: 10.2174/1570159x15666170724104305
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by (endo)Cannabinoids in Glaucoma and Retinal Neurodegenerative Diseases

Abstract: The aim of this review is to present a modern view of the endocannabinoid system, in order to discuss in a better perspective available data from preclinical studies on the use of eCBs as new neuroprotective agents, potentially useful to prevent glaucoma and retinal neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 149 publications
0
45
0
1
Order By: Relevance
“…Long-term oral treatment with CBD for 8 months also prevented deficits of social recognition memory in transgenic AβPPSwe/PS1ΔE9 (AβPP × PS1) mice ( Cheng et al, 2014c ) and using the same model, but treating the animals daily with intraperitoneal injections of CBD for 3 weeks, Cheng et al (2014a) reported that CBD reversed social and novel object recognition deficits without affecting anxiety-related behaviors. In addition, the presently reported ability of AEA to blunt the enlargement of the brain ventricles suggests an indirect preventive action against neuronal death, which is a well-reported neuroprotective feature of endocannabinoids ( Rapino et al, 2017 ; Vrechi et al, 2018 ), including AEA ( Xu et al, 2017 ). Further analysis of specific markers of neurodegeneration such as Fluorojade, caspase-3 and Bax, which are increased by icv-STZ ( Espinosa et al, 2013 ; Song et al, 2014 ; Biswas et al, 2016 ), would be interesting to better understand the mechanisms behind the neuroprotective role of AEA against the ventricle enlargement.…”
Section: Discussionmentioning
confidence: 94%
“…Long-term oral treatment with CBD for 8 months also prevented deficits of social recognition memory in transgenic AβPPSwe/PS1ΔE9 (AβPP × PS1) mice ( Cheng et al, 2014c ) and using the same model, but treating the animals daily with intraperitoneal injections of CBD for 3 weeks, Cheng et al (2014a) reported that CBD reversed social and novel object recognition deficits without affecting anxiety-related behaviors. In addition, the presently reported ability of AEA to blunt the enlargement of the brain ventricles suggests an indirect preventive action against neuronal death, which is a well-reported neuroprotective feature of endocannabinoids ( Rapino et al, 2017 ; Vrechi et al, 2018 ), including AEA ( Xu et al, 2017 ). Further analysis of specific markers of neurodegeneration such as Fluorojade, caspase-3 and Bax, which are increased by icv-STZ ( Espinosa et al, 2013 ; Song et al, 2014 ; Biswas et al, 2016 ), would be interesting to better understand the mechanisms behind the neuroprotective role of AEA against the ventricle enlargement.…”
Section: Discussionmentioning
confidence: 94%
“…These variations make the accurate diagnosis extremely challenging. In clinical settings, no medication can halt the photoreceptor death and visual devastations in RP patients (Khan et al, 2017;Rapino et al, 2018). Accumulating evidences suggest that the oxidative stress contributes to the photoreceptor apoptosis of RP.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that activation of cannabinoid receptors decreases aqueous humor production and increases trabecular and uveoscleral outflow, thereby reducing intraocular pressure (IOP) . Recent studies suggest that activation of cannabinoid receptor may feature IOP independent effects, such as neuroprotective properties or improvement in ocular hemodynamics . In particular, the finding that activation of cannabinoid receptors show vasoactive actions in isolated perfused retinal arterioles makes it an interesting target to alter ocular blood flow independent of IOP …”
mentioning
confidence: 99%